2021
DOI: 10.1126/sciadv.abj2515
|View full text |Cite
|
Sign up to set email alerts
|

Serpentinite-derived slab fluids control the oxidation state of the subarc mantle

Abstract: Recent geochemical evidence confirms the oxidized nature of arc magmas, but the underlying processes that regulate the redox state of the subarc mantle remain yet to be determined. We established a link between deep subduction-related fluids derived from dehydration of serpentinite ± altered oceanic crust (AOC) using B isotopes and B/Nb as fluid proxies, and the oxidized nature of arc magmas as indicated by Cu enrichment during magma evolution and V/Yb. Our results suggest that arc magmas derived from source r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…Thus, owing to the strong oxidizing capacity of sulfate (Benard et al., 2018; Debret & Sverjensky, 2017; Evans & Tomkins, 2011), the release of sulfate‐rich fluids during serpentinite dehydration and their subsequent infiltration into the overlying mantle wedge may be essential for the oxidation of the sub‐arc mantle. In this context, primitive arc magmas in warm subduction zones are likely less oxidized overall than those in cold subduction zones (Zhang, Gazel, et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, owing to the strong oxidizing capacity of sulfate (Benard et al., 2018; Debret & Sverjensky, 2017; Evans & Tomkins, 2011), the release of sulfate‐rich fluids during serpentinite dehydration and their subsequent infiltration into the overlying mantle wedge may be essential for the oxidation of the sub‐arc mantle. In this context, primitive arc magmas in warm subduction zones are likely less oxidized overall than those in cold subduction zones (Zhang, Gazel, et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Arc magmas from cold subduction zones in the western Pacific are systematically enriched in Cu at intermediate MgO concentrations, indicating that their primitive magmas were initially sulfide undersaturated (Chiaradia, 2014; Jenner et al., 2010; Lee et al., 2012) and likely oxidized (Kelley & Cottrell, 2009; Zhang, Gazel, et al., 2021). Moreover, these arc magmas are characterized by high B/Nb ratios and heavy B isotopic compositions, suggesting that serpentinite‐derived fluids affected their mantle sources (De Hoog & Savov, 2018; Zhang, Gazel, et al., 2021), which may control their oxidized nature (Zhang, Gazel, et al., 2021). These characteristics make western Pacific subduction zones ideal for investigating whether the dehydration of subducted serpentinite releases oxidized sulfate‐rich fluids into the sub‐arc mantle.…”
Section: Introductionmentioning
confidence: 99%
“…The increasingly hydrous nature of magmas produced at NLV correlate with a sustained increase in oxygen fugacity (Figure 8). This association of fluid signature and oxidation state of magmas has been observed in regional comparisons among arcs through different proxies and approximations (Kelley and Cottrell, 2009;Evans et al, 2012;Zhang et al, 2021), although there is little consensus on the nature of the processes that link hydrous fluids to oxidation state. Proposed mechanisms range from direct supply of Fe 3+ and other oxidizing agents from the oceanic crust and sediments to the asthenospheric mantle (Mungall, 2002), to H 2 O dissociation into O 2 and H + , with either degassing or capture of the latter into mineral phases, to preferential removal of Fe 2+ by fractionating phases.…”
Section: Origin Of Mafic Magmasmentioning
confidence: 91%
“…However, there is a continuing debate on whether the redox state of fluid speciation is oxidized or reduced. Most previous studies on fluid inclusions in highpressure (HP) metamorphic rocks, experiments, isotope evidence, and thermodynamic calculations suggested that the slab-derived fluids are highly oxidized (Scambelluri and Philippot, 2001;Frezzotti et al, 2011;Frezzotti and Ferrando, 2015;Pons et al, 2016;Rielli et al, 2017;Gerrits et al, 2019;Walters et al, 2020a;Iacovino et al, 2020;Maurice et al, 2020;Zhang et al, 2021;Ague et al, 2022), whereas some argued for rather reduced fluids (Song et al, 2009;Frezzotti and Ferrando, 2015;Brovarone et al, 2017;Tao et al, 2018;Chen et al, 2019;Piccoli et al, 2019;. As a result, the redox state of slab-derived fluids is proposed to have a broad fO 2 range varying from △FMQ+5 to △FMQ-4 (e.g., Evans and Powell, 2015;Debret and Sverjensky, 2017;Piccoli et al, 2019;Walters et al, 2020b;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%